THE EFFECT OF NITRATE-BASED NPK FERTILIZER ON THE GROWTH AND YIELD OF RED ONION (Allium ascalonicum L.) PLANT AT PT PUPUK KUJANG CIKAMPEK - Nurmeilani, Mila; Syah, Bastaman; Sugiono, Darso; Jiwa, Rangga (Jurnal Ilmiah Hijau Cendekia, 2024)
Shallots (Allium ascalonicum L.) is one of the horticultural crop commodities that is widely consumed. One factor to overcome the level of soil fertility is by providing sufficient fertilizer to restore soil fertility. Fertilizer is the main source of nutrients which are very important for plant growth and yields. This research aims to determine the response of shallot plants (Allium ascalonicum L.) to the application of nitrate-based NPK fertilizer. This trial will be carried out at the PT Pupuk Kujang Cikampek Screenhouse, from October to December 2023. This research used the Completely Randomized Design (CRD) method. There are 6 treatments, namely P0 (control), P1 (Nitrea Urea 0.4g + Phonska 15-10-12 0.6g + NPK Merauke 0.6g + KCl 0.2g), P2 (Nitrea Urea 0.4g + Phonska 15 -10-12 0.6g + NPK Nitroku 0.6g + KCl 0.2g), P3 (Nitrea Urea 0.4g + Phonska 15-10-12 0.6g + NPK 10-10-10 0.6g + KCl 0 .2g), P4 (Nitrea Urea 0.4g + Phonska 15-10-12 0.6g + NPK 10-10-10 0.8g + KCl 0.2g), P5 (Nitrea Urea 0.4g + Phonska 15-10 -12 0.6g + NPK 10-10-10 1g + KCl 0.2g). Each treatment was repeated 4 times to obtain 24 experimental units. The experimental results showed that the application of nitrate-based NPK fertilizer was not able to have a real effect on the growth and yield of shallot plants (Allium ascalonicum L.) for all observations.